Measurement Error of a Coupled AFM Probe-Elastic Membrane System. (2nd September 2018) - Lin, Shueei-Muh; Tsai, Che-Lun; Lee, Hung-Chang
Abstract : The characteristic of an AFM probe scanning the topography on an elastic substrate is investigated. It is different to the conventional rigid substrate. The analytical solution of the novel system is presented. For an elastic substrate the errors of frequency shift determined by using the force gradient methods and the perturbation method are satisfactory only for larger tip-surface distances. The smaller the interacting distance is, the larger the measurement error due to the amplitude of membrane is.